A PERSPECTIVE STUDY IN THE ERA OF SOCIAL MEDIA BOOMING; HOW STUDENTS DISTINGUISHING FACTS AND MISINFORMATION? - Mohd Harris Bin Md Salleh; Wan Afra Binti Ibrahim (Jurnal Penyelidikan Sains Sosial, 2021)
Reading culture in many literatures has proven to be a key to success. In the newlandscape of information booming catalysed by the progress of internet of things, the paradigmand mechanics of reading have also entering the new level. The purpose this study is toinvestigate the cultural change of reading and its patterns. Another aspect that is also takeninto our focus of study is the students’ attitude on how do they accept information anddistinguish between facts and misinformation. 175 respondents among semester 1 students fromPoliteknik Tun Syed Nasir Ismail become the subjects of this research. Mix methodology ofcombining quantitative and qualitative approach have been used to sought data. Data is furtheranalysed using statistical software to come to the findings of research. Results suggest students’behaviour and attitude and level of acceptance of information are vary among students.Significant finding between high and low achievers has shown a distinctive attitude andstrategies towards distinguishing facts and misinformation.